Difficult asthma in children - Lis, Grzegorz (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2009)
The assessment of patients with difficult asthma comprises three major issues: 1) does the patient really have asthma, 2) is the patient compliant with prescribed therapy, and 3) are there any environmental or co-morbid factors worsening asthma?